1985
DOI: 10.1080/15298668591395409
|View full text |Cite
|
Sign up to set email alerts
|

Formaldehyde: A Comparative Evaluation of Four Monitoring Methods

Abstract: The performances of four formaldehyde monitoring devices were compared in a series of laboratory and field experiments. The devices evaluated included the DuPont C-60 formaldehyde badge, the SKC impregnated charcoal tube, an impinger/polarographic method and the MDA Lion formaldemeter. The major evaluation parameters included: concentration range, effects of humidity, sample storage, air velocity, accuracy, precision, interferences from methanol, styrene, 1,3-butadiene, sulfur dioxide and dimethylamine. Based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Although the authors did not find published studies directly, and comprehensively comparing the methods referred to in the OSHA manuals, indirect mentions in two publications suggest absence of any important bias. (25,26) A small OSHA study about validation of a diffusive sampler reported, based on 10 samples, a slight downward bias (5-10%) of the impinger method compared with the XAD-2 method (the standard error of the XAD-2 method is 7%). (27) The authors assumed comparability of the methods in this study's analysis.…”
Section: Statistical Modelingmentioning
confidence: 99%
“…Although the authors did not find published studies directly, and comprehensively comparing the methods referred to in the OSHA manuals, indirect mentions in two publications suggest absence of any important bias. (25,26) A small OSHA study about validation of a diffusive sampler reported, based on 10 samples, a slight downward bias (5-10%) of the impinger method compared with the XAD-2 method (the standard error of the XAD-2 method is 7%). (27) The authors assumed comparability of the methods in this study's analysis.…”
Section: Statistical Modelingmentioning
confidence: 99%
“…Positive interferences have been reported from methanol, styrene, 1,3-butadiene and so2. (8) Interferences from phenol, resorcinol, formic acid and furfuryl alcohol were reported for an earlier model. (3) A special filter is now available to minimize phenol interferences.…”
Section: Other Portable Voc Monitoring Instrumentsmentioning
confidence: 83%
“…This instrument has been reported to be linear over the range of 0.4 to Sppm formaldehyde with an accuracy of 99 ± 20% over this range. (8) The lower limit of detection is 0.3 ppm. Positive interferences have been reported from methanol, styrene, 1,3-butadiene and so2.…”
Section: Other Portable Voc Monitoring Instrumentsmentioning
confidence: 99%